Analisis Pengaruh Loyalitas Penggguna Media Streaming dengan Teori Repeat Patronage - Sudarmawan, Wahyu (Jurnal Komunikasi, 2023)
New media has transformed people's behavior in using media. The ways people use old media were different from new media. Compared to old media, new media users are more active in choosing the desired media content. The choice of new media content is also much more diverse. This research aims to analyze the repeated patronage model on the loyalty of online media users, especially streaming media. The research was conducted using a quantitative approach. Data is collected through surveys. A sample of 100 respondents was collected through purposive sampling. Data analysis was carried out using the Partial Least Square (PLS) approach. The research results show that relative attitudes have a significant positive effect on the loyalty of online media users. Social norms and situational factors were not found to moderate the influence of relative attitudes on audience loyalty. This shows that social norms and situational factors are not moderators of the influence of relative attitudes on loyalty. Based on these results, the concept of repeat patronage is not good at explaining user loyalty to online media.